In vitro Release Kinetics Study of Diclofenac Sodium from Acrylic Polymer Coated Pellets - Kibria, Golam; Jalil, Reza-ul (Dhaka University Journal of Pharmaceutical Sciences, 2007)
The aim of the present study is to investigate the effect of Ammonio Methacrylate Copolymer Type B (Eudragit RS 30 D) on the release kinetics study of diclofenac sodium form coated pellets. The effect of the incorporation of xanthan gum into the coating formulation was also the goal of this study. Eudragit RS 30 D and xanthan gum was added into the formulation at 5:1 ratio. Different percent of this polymeric combination was loaded on to the drug-loaded pellets. It was found that the cumulative % release of drug decreased with the increase of polymer load in all cases. From all formulations it was observed that the release of diclofenac sodium in 0.1N HCl media was very low (maximum 3.5%) at first 2 hours. Better sustaining effect was found from Eudragit RS 30 D and xanthan gum combinations. Drug was released linearly along with time throughout the whole dissolution process in phosphate buffer (pH 6.8) and it was also revealed that, in all cases the release of diclofenac sodium followed mixed release kinetics but zero order release kinetics predominates. Key words: Diclofenac sodium, pellets, sustained release, in vitro, kinetic analysis. Dhaka Univ. J. Pharm. Sci. 6(1): 1-7, 2007 (June)The full text is of this article is available at the Dhaka Univ. J. Pharm. Sci. website